Bureaucratic Reform Barriers: A Case Study on the One Stop-Integrated Service Office in Bone Regency - Yusri Adi (Magister Ilmu Administrasi Publik, 2018)
This research aimed at identifying the barriers to the implementation of bureaucratic reform, exploring the factors that cause these obstacles and offering some solutions to improve licens-ing administration services, this research applied the descriptive-qualitative approach using the case study design. Techniques of collecting data included interview, observation, and documen-tation. Instruments in this research, added the researcher himself (key device), an informant who was selected based on purposive sampling technique. Data analysis was based on